Analisis Perbandingan Nilai Tambah Produk UMKM Berbasis Tepung Mocaf VS Non Mocaf di Kota Palembang - Chany Melva Apelin Panjaitan; Erni Purbiyanti (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Cassava has the potential to improve farmers' livelihoods, support micro, small, and MSMEs, and contribute to national foreign exchange through high-value processed products. This research was conducted to calculate and compare the magnitude of added value generated by MSMEs from processing MOCAF and non-MOCAF flour into final products. The study was carried out at three MSMEs located in Palembang City: MSME 1 in 7 Ulu Village, MSME 2 in Bukit Baru Village, and MSME 3 in the Golden Estate Housing Complex. The research period spanned from August 2023 to January 2024. A case study approach was employed in this research, with the owners of each MSME server serving as respondents. The data collected consisted of two types: primary and secondary data. Hayami's method and descriptive tabular comparison analysis were used to analyze the data. The results show that processed mocaf flour products demonstrate a higher added value compared to non-mocaf products. Mocaf-based pempek generates the highest added value due to its relatively higher selling price, followed by cookies and stik. Overall, mocaf-based products are more profitable and offer positive economic, social, environmental, and health impacts.